2015
DOI: 10.1097/ajp.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Coping, Pain, and Activity After Cognitive-Behavioral Training

Abstract: Objectives We examined the outcomes of a cognitive-behavioral therapy (CBT) intervention for pain in pediatric sickle cell disease (SCD) using smartphones as a novel delivery method. Methods Forty-six children with SCD received CBT coping skills training using a randomized, waitlist control design. The intervention involved a single-session of CBT training and home-based practice using smartphones for eight weeks. Pre-post questionnaires between the randomized groups were used to evaluate changes in active p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 51 publications
2
104
2
Order By: Relevance
“…Therefore, description of results but no graphic representation was possible [ 26 ]. Schatz et al [ 24 ] did not compare baseline to follow-up mean pain values, and consequently, the study could also not be included in the graphical representation. Authors of studies with missing data were contacted through email (corresponding email address on publication), but none of them responded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, description of results but no graphic representation was possible [ 26 ]. Schatz et al [ 24 ] did not compare baseline to follow-up mean pain values, and consequently, the study could also not be included in the graphical representation. Authors of studies with missing data were contacted through email (corresponding email address on publication), but none of them responded.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed a statistically significant decrease in chronic pain; the other showed no decrease in patients with acute pain [ 28 , 29 ]. Schatz et al [ 24 ] did not report about the severity of pain at baseline and follow-up. Therefore, we were not able to depict the results graphically.…”
Section: Resultsmentioning
confidence: 99%
“…Only a handful of apps are relevant to CBT homework and all of these are in the early stages of development. Of those designed for adolescents, several focus specifically on self-monitoring: Mobile Mood Diary [49,50], mobiletype [51-55], and a daily pain diary [56,57]. Research on these tools suggests that they are useful and acceptable to adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Mood graphs appeared to facilitate discussion in the therapy session. An intervention to facilitate self-monitoring as well as skills practice for pain management was evaluated as usable and acceptable by adolescents and their parents, and preliminary evidence indicated that it had a beneficial effect on coping skills [57]. …”
Section: Introductionmentioning
confidence: 99%
“…25 Also, pain is a subjective experience; thus, guardian-report may have led to underestimates of youth pain as it would be reflective of guardian observed pain behaviors and pain as reported to the guardian by the youth. However, parentproxy reports for pain experiences are commonly used and have been validated for pediatric pain populations, 26,27 and the measure used in the current study has been validated for youth with SCD and used across multiple studies, [28][29][30][31] allowing for comparison of findings. Still, future studies should incorporate youth reports of their pain.…”
Section: Discussionmentioning
confidence: 99%